Metode Dubbing dan Subtitling dalam Pembelajaran Bahasa Inggris - Widya; Agustiana, Erika (Politeknik Bina Madani, 2023)
Abstract. Several media that can be utilized for English language learning in the classroom include audio-visual media, flashcards, interactive maps, and more.Among the audio-visual media, films are noteworthy. Through films, teachers encourage students to grasp the storyline by reading English subtitles. Dubbing isa technique used to mimic the voices of actors in the film, sparking students' interest in English communication. On the other hand, subtitling involves transcribing film dialogues displayed at the bottom of the screen. Students can participate in diverse activities to improve their English comprehension. Thesemethods enable students to enrich their vocabularies, practice pronunciation, and enhance literacy. Teachers may also assign tasks for students to write about the moral lessons learned from the films. Numerous other engaging activities can be incorporated through these methods to bolster students' understanding of learning English.